Research-practice partnerships: a strategy for promoting educational recovery - Ainscow, Mel (Perspectiva Educacional, 2023)
This paper argues that efforts to help education systems recover following the recent global pandemic should involve collaboration amongst schools, and partnerships between practitioners and academic researchers. Drawing on a series of projects carried out over the last three decades, this approach is defined as a process of knowledge-generation that occurs when researcher and practitioner knowledge meet in particular sites. Underlying these collaborations is a common pattern. Most importantly, they involve an engagement with evidence collected by practitioners with support from university researchers. The paper points to the potential benefits of the approach, whilst also throwing light on some of the challenges involved.